1985
DOI: 10.1007/bf01893099
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cecal volvulus by multiple barium enemas

Abstract: It has been frequently stated that barium enema has no value in the treatment of cecal volvulus. We present a patient with cecal volvulus who was effectively treated by barium enema; however, multiple studies were required to achieve optimal results. In a subset of patients with cecal volvulus, laparotomy may be avoided by the use of barium enema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Non-operative reduction of caecal volvulus (eg, by colonoscopy or contrast enema) is rarely successful (<5 %) and could cause perforation. In addition, colonic necrosis may be missed in 20%–25% of patients who undergo non-operative reduction, and such patients may develop colonic perforation 13 19 26 29 30. Surgical approaches to caecal volvulus vary depending on intraoperative findings and patient stability, typically right hemicolectomy with or without ileostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Non-operative reduction of caecal volvulus (eg, by colonoscopy or contrast enema) is rarely successful (<5 %) and could cause perforation. In addition, colonic necrosis may be missed in 20%–25% of patients who undergo non-operative reduction, and such patients may develop colonic perforation 13 19 26 29 30. Surgical approaches to caecal volvulus vary depending on intraoperative findings and patient stability, typically right hemicolectomy with or without ileostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors feel barium enema should be avoided in cecal volvulus, as it is of little therapeutic value and is potentially dangerous in view of the 25% incidence of gangrenous bowel 4 . However, others have found barium enema to be diagnostic in a significant percentage of cases, 9 , 14 and some authors have reported the reduction of cecal volvulus by multiple barium enemas 15 . If barium enema is not used, sigmoidoscopy may be useful in order to rule out a distal obstructing lesion 1 …”
Section: Discussionmentioning
confidence: 99%
“…Surgery remains the treatment of choice [3]. Attempts at nonsurgical Because patIents wIth cecal volvulus are acutely Ill and management in poor-risk surgical candidates have had limited have a hIgh surgical mortality, treatment has been by means success [4,5]. We report successful use of anterior percuof a banum enema or colonoscopy [4,5].…”
mentioning
confidence: 99%